Reasonable Partiality and Animal Ethics - Rollin, Bernard E. (Ethical theory and moral practice, 2005)
Moral psychology is often ignored in ethical theory, making applied ethics difficult to achieve in practice. This is particularly true in the new field of animal ethics. One key feature of moral psychology is recognition of the moral primacy of those with whom we enjoy relationships of love and friendship – philia in Aristotle’s term. Although a radically new ethic for animal treatment is emerging in society, its full expression is severely limited by our exploitative uses of animals. At this historical moment, only the animals with whom we enjoy philia – companion animals – can be treated with unrestricted moral concern. This ought to be accomplished, both for its own sake and as an ideal model for the future evolution of animal ethics.